Determination of carbamazepine in serum and saliva samples by high performance liquid chromatography with ultraviolet detection - Đorđević Snežana; Kilibarda Vesna; Stojanović Tomislav (Vojnosanitetski Pregled)
Background/Aim. Carbamazepine is antiepileptic drug widely used for the treatment of epilepsy. Due to low therapeutic index of carbamazepine there is a need for routine measuring its concentrations in biological fluids. The aim of the study was to describe a method for concomitant determination of carbamazepine in the serum and saliva. Methods. Separation of the drug from matrix is achieved by reversedphase chromatography on a C18 column, with a mobile phase of methanol-water-acetic acid (65:34:1) at a flow-rate of 1.0 ml/min. Detection was effected by ultra-violet absorption at 285 nm. The total run time was 5 min. Samples were prepared by alkaline extraction (pH 10) using chlorophorm. Results. Calibration curves were in the range 0.1-5 μg/mL for serum and saliva samples. Mean recoveries of spiked serum and saliva were 97.59 and 92.30%, respectively. Limits of detection (LOD) of carbamazepine in serum and saliva were 0.166 and 0.178 μg/mL, respectively. Limits of quantification (LOQ) in the serum and saliva were 0.237 and 0.226 μg/mL, respectively. The method precision was carried out with coefficient of variation of 2.10% and 4.03% for the serum and saliva, respectively. The obtained data showed that there was a strong correlation between saliva and serum concentrations (r = 0.9481, p < 0.001). Conclusion. The method described here is rapid, precise, accurate and simple, and can be used for quantitative determination of carbamazepine in human serum and saliva after therapy applying. Saliva samples could be used as an alternative matrix for therapeutic drug monitoring of this antiepileptic drug.